Aflasafe GH01 and Aflasafe GH02 for Ghana - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, an additional distribution partner was appointed to distribute Aflasafe GH01 and Aflasafe GH02 for use in groundnuts, maize, and sorghum plus public and private sector actors launched initiatives to help scale Aflasafe and increase awareness and capacity. Since 2018, the products have been distributed by Macrofertil Ghana Ltd.